Overview of MicroRNA Biology - Mohr, Ashley M.; Mott, Justin L. (Seminars in Liver Disease, 2015)
In considering an overview of microRNA biology, it is useful to consider microRNAs as a part of cellular communication. At the simplest level, microRNAs act to decrease the expression of messenger RNAs that contain stretches of sequence complementary to the microRNA. This function can be likened to the function of endogenous or synthetic short interfering RNA. However, microRNA function is more complicated and nuanced than this “on–off” model would suggest. Further, many microRNA targets are themselves noncoding RNAs. In this review, the authors discuss the role of microRNAs in shaping the proteome of the cell in a way that is consistent with microRNA involvement in a highly regulated conversation, sensitive to outside influence and internal feedback.
Keywords: ribonucleoprotein; long noncoding RNA; RNAi; microRNA; alternatives to seed binding